Management of Use of E-Learning Applications in Pack C Equality Education in Improving Student Learning Quality - Minda Patriah; Achmad Sanusi; Nanang Hanafiah; Supyan Sauri (Journal of Islamicate Studies, 2022)
Management of the utilization of e-learning applications on the equality of package C in improving the quality of s.swa learning. After going through field observation activities, interviews with resource persons, as well as documentation analysis at PKBM Pelita Pratama and PKBM Homeschooling Millennial Unggul, an overview of the Study on the management of the utilization of e-learning applications in equality education to improve the quality of student learning as follows: Both institutions have fulfilled the stages of management starting with the E-Learning Application Planning on Equality Package C education in Improving the Quality of Student Learning. Includes Computer Device Devices, Internet Networks, Learning materials, Module Tutorials, Audio Video, Organizing includes Assignment (Rombel).